A numerical study of forced convection from an isothermal cylinder performing rotational oscillations in a uniform stream. (December 2018) - Mittal, H.V.R.; Al-Mdallal, Qasem M.
Highlights: The problem of forced convection from a heated cylinder performing rotational oscillation motion in a uniform stream has been numerically investigated using a transformation-free HOC scheme. Comparisons with others numerical and experimental results verify the accuracy of the present numerical algorithm. The effects of maximum angular velocity of the cylinder and forced oscillation frequency on the heat transfer rate are discussed. A detailed discussion of heat transfer coefficients within the lock-on ranges is presented to build a connection between the heat transfer and the lock-on regimes. Abstract: Forced convection from a heated rotationally oscillating circular cylinder placed in a uniform cross flow of constant properties fluid is investigated. The two-dimensional governing equations of flow motion and energy are solved numerically on non-uniform polar grids using a higher order compact (HOC) formulation. The flow and thermal fields are mainly influenced by Reynolds number, Re, Prandtl number, Pr, maximum angular velocity of the cylinder, α m, and the frequency ratio, f / f 0, which represents the ratio between the oscillation frequency, f, and the natural vortex shedding frequency, f 0 . The numerical simulations are performed at Re = 200, Pr = 0.5 - 1.0, α m ∈ [ 0.5, 4.0 ] and f / f 0 ∈ [ 0.5, 3.0 ] . The resulting lock-on phenomena behind the cylinder is detected and thermal field is determined. Comparisons with previous numerical and experimental results verify the accuracy and the reliability of the present study. Variations in heat transfer coefficients within the lock-on ranges are investigated to build a connection between the heat transfer and the lock-on regimes.